Dampak Kejadian Bullying Terhadap Perkembangan Sosial Emosional pada Anak Usia Dini di TK Pelita Desa Ubung Kaja: The Impact of Bullying on Early Childhood Social-Emotional Development at Pelita Kindergarten, Ubung Kaja Village - Ni Luh Ayu Ariasih; Ida Bagus Komang Sindu Putra (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2025)
Early childhood social and emotional development is part of the aspects of development in children that are closely related to the concept of socializing and emotions in children, it needs to be considered and directed so that its development becomes better over time and the increasing age of the child. During the age of children, especially at the age of 0 to 8 years, individuals are said to be early childhood who are vulnerable to the scope of friendship with play periods that are vulnerable to Bullying or Bullying behavior. Bullying has several forms, namely physical, verbal, and other forms. To prevent and deal with Bullying behavior in early childhood, it is necessary to contribute and coordinate between parents and teachers at school by giving children a firm understanding not to repeat it. Because Bullying behavior has a negative impact on the social-emotional development of Bullying perpetrators and victims of Bullying who are still at an early age. This research was conducted at TK Pelita Desa Ubung Kaja. This research method uses a qualitative method with the stages of observation of Bullying behavior in children and literature studies regarding Bullying cases that occur in early childhood from various scientific sources.   ABSTRAK  Perkembangan sosial emosional anak usia dini merupakan bagian dari aspek perkembangan pada anak yang erat kaitannya dengan konsep bersosialisasi dan emosi pada anak, perlu diperhatikan dan diarahkan agar perkembangannya menjadi lebih baik seiring dengan berjalannya waktu dan bertambahnya usia anak. Pada masa usia anak-anak khususnya pada usia 0 hingga 8 tahun, individu dikatakan sebagai anak usia dini yang rentan dengan ruang lingkup pertemanan dengan masa bermain yang rentan dengan perilaku Bullying atau perundungan. Bullying memiliki beberapa bentuk, yaitu fisik, verbal, dan bentuk lainnya. Untuk mencegah dan menangani perilaku Bullying pada anak usia dini, perlu adanya kontribusi dan koordinasi antara orang tua dan guru di sekolah dengan memberikan pemahaman yang tegas kepada anak untuk tidak mengulanginya. Karena perilaku Bullying memiliki dampak negatif bagi perkembangan sosial emosional pelaku Bullying dan korban Bullying yang masih berusia dini. Penelitian ini dilakukan di TK Pelita Desa Ubung Kaja. Metode penelitian ini menggunakan metode kualitatif dengan tahapan observasi perilaku Bullying pada anak dan studi literatur mengenai kasus Bullying yang terjadi pada anak usia dini dari berbagai sumber ilmiah.